Konsep Riba dalam Perspektif Hadis - Taufiq, Moch Imron (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the concept of usury in the perspective of hadith. This study uses a qualitative type through literature study by applying content analysis. The discussion of this research includes general views on usury, takhrij hadith about the prohibition of usury, and the concept of the prohibition of usury. The conclusion of this study shows that usury is unlawful and in the hadiths of usury eaters, people who order usury to eat, their clerks and their witnesses are cursed by the Prophet sallallaahu 'alaihi wasallam. This research is expected to have benefits for enriching the treasures of Islamic knowledge.